Perancangan Produk Rak Melalui Pendekatan Design Berbasis Eksperimen - Resmelani Septia; Andry Masri (Jurnal Desain Indonesia., 2025)
This study focuses on the development of innovative shelf designs by utilizing the bending lamination technique on corn cobs. The design method used is a direct experiment-based design method involving five stages, starting with the empathize stage and ending with the testing stage through market testing through exhibitions. The main strategy in this design research is optimizing the use of corn cobs formed with a 35 cm diameter cylindrical mold made of stainless steel. The output of the study is a shelf prototype made of corn cobs produced through the bending lamination technique combined with teak wood and multiplex as product supports. An important finding of this study is the optimization of the bending lamination technique in making shelves that offer creative novelty value. This research was conducted at PT. Matahati Kreasi Nusantara for one month. Keywords: Corn Cob Shelves, Corn Cob Creative Novelty, Corn Cob Lamination Bending Technique.